Pleiotropic Effects of Heparin and its Monitoring in the Clinical Practice - Arachchillage, Deepa J.; Kitchen, Steve (Seminars in Thrombosis and Hemostasis, 2024)
Unfractionated heparin (UFH) was uncovered in 1916, has been used as an anticoagulant since 1935, and has been listed in the World Health Organization's Model List of Essential Medicines. Despite the availability of many other anticoagulants, the use of heparin (either low molecular weight heparin [LMWH] or UFH) is still substantial. Heparin has pleotropic effects including anticoagulant and several nonanticoagulant properties such as antiproliferative, anti-inflammatory activity, and anticomplement effects. Although UFH has been widely replaced by LMWH, UFH is still the preferred anticoagulant of choice for patients undergoing cardiopulmonary bypass surgery, extracorporeal membrane oxygenation, and patients with high-risk mechanical cardiac valves requiring temporary bridging with a parenteral anticoagulant. UFH is a highly negatively charged molecule and binds many positively charged molecules, hence has unpredictable pharmacokinetics, and variable anticoagulant effect on an individual patient basis. Therefore, anticoagulant effects of UFH may not be proportional to the dose of UFH given to any individual patient. In this review, we discuss the anticoagulant and nonanticoagulant activities of UFH, differences between UFH and LMWH, when to use UFH, different methods of monitoring the anticoagulant effects of UFH (including activated partial thromboplastin time, heparin anti-Xa activity level, and activated clotting time), while discussing pros and cons related to each method and comparison of clinical outcomes in patients treated with UFH monitored with different methods based on available evidence.
Keywords: unfractionated heparin; activated partial thromboplastin time; heparin anti-Xa; activated clotting time; pleotropic effects